2021
DOI: 10.1016/j.actamat.2020.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Fracture mechanism and toughness of a rolled magnesium alloy under dynamic loading

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…In this work, J p has been used to estimate the crack energy release rate since previous studies have shown that the contribution of the elastic part (J e ) in the determination of J is negligible. Evaluation of J p is done as follows (Sreedhar et al 2021):…”
Section: Fracture Toughness Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, J p has been used to estimate the crack energy release rate since previous studies have shown that the contribution of the elastic part (J e ) in the determination of J is negligible. Evaluation of J p is done as follows (Sreedhar et al 2021):…”
Section: Fracture Toughness Testmentioning
confidence: 99%
“…In the above equation, factor r (0 \ r \ 1) is taken as 0.4, which represents the location of the hinge point ahead of the crack tip. The critical amount of energy release rate (J IC ) has been taken as that value of J p from where crack initiation takes place in samples as reported in previous literature (Sreedhar et al 2021). Additionally, it has been reported in the previous studies that J IC is the term that remains independent of specimen geometry when compared to other terms that give a parameter to quantify fracture toughness (Fro ´meta et al 2020).…”
Section: Fracture Toughness Testmentioning
confidence: 99%